2015
DOI: 10.1016/j.lungcan.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

CT screening for lung cancer: Importance of emphysema for never smokers and smokers

Abstract: Identification of emphysema in low-dose CT scans increases the risk of lung cancer and is important in determining follow-up of current, former, and never smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 25 publications
5
39
0
Order By: Relevance
“…The prevalence of COPD in our study is consistent with some previous results, but slightly lower than others [12, 13, 34]. Even so, we found high rates of underdiagnosis (71.6%), consistent with the available data from other series [34-37].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The prevalence of COPD in our study is consistent with some previous results, but slightly lower than others [12, 13, 34]. Even so, we found high rates of underdiagnosis (71.6%), consistent with the available data from other series [34-37].…”
Section: Discussionsupporting
confidence: 93%
“…The remaining smokers were classified as ex-smokers. Never smokers were defined as having smoked less than 100 cigarettes in their lifetime [12]. Spirometry was performed at the LC diagnosis by a technician specialized in respiratory functional tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD and interstitial lung disease are also strong risk factors for lung cancer [21][22][23] . Henschke et al [24] found that the prevalence of lung cancer increased among those who had CT evidence of emphysema immaterial of smoking status. In our study, malignant nodules tended to have severe regional emphysema and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…b Major benefits in terms of reduction of other smoking-related diseases; the potential to utilise lung CT screening to diagnose coronary artery calcification, COPD [31,32,33], and potentially in breast cancer and spinal stenosis. Further research is required to direct EU policy on these added benefits.…”
Section: Resource Allocation Which Maximizes the Eu Commission Actiomentioning
confidence: 99%